(untitled) (European Journal of Marketing and Economics, 2026)
Firms often use semiotic cues, such as colours associated with foreign national identities, to influence consumers’ perceptions of a product’s country of origin. This study investigates whether incorporating the colours of the Italian flag on olive oil packaging alters American consumers’ perceptions of origin and how these perceptions affect downstream evaluations within the Stimulus-Organism-Response (SOR) framework. A quasi-experimental design using fictitious packaging was administered to U.S. consumers (n = 231) via MTurk. Although the stimulus successfully shifted perceived origin toward Italy, perceived origin did not significantly influence perceived quality, involvement, or brand trust. When the true origin (Portugal) was revealed, consumer evaluations did not deteriorate; instead, willingness to pay increased. These results suggest that semiotic cues can shape perceived origin but may not generate deeper evaluative effects unless strongly aligned with category-specific expectations. The study contributes to semiotics and country-of-origin research by demonstrating that symbolic cues may influence perception without affecting internal evaluations, and that origin disclosure does not necessarily elicit negative reactions. Insights into international branding strategies are discussed.